Penguatan Manajemen Pangan Berkelanjutan melalui Branding dan Teknologi Digital Nelayan Lere Palu - Zainuddin, Zulkifli; Tohiroh , Tohiroh; Putra, Agung Laksono; Kultsum, Ummi (Jurnal Nusantara Mengabdi, 2025)
Purpose: Local food availability in Central Sulawesi faces post-disaster challenges and global market competition. This community service program aims to improve the competitiveness of Lere Village fishermen's food products through branding strategies and the use of digital technology. Methodology/approach: The program was implemented through community outreach, targeted training sessions, and mentoring focused on basic business management, digital marketing, and product quality improvement. Twenty-five fishermen participated in this program, selected based on their direct involvement in local food production and distribution. Results/findings: Results showed an increased management, product packaging, and skills in using social media for promotion. Partners also received product diversification strategies and access to food certification. Conclusions: In conclusion, this program has had a positive impact in increasing the capacity of fishermen to manage local food businesses and expand markets, thus supporting food sustainability in Central Sulawesi. Limitations: This program has limitations in the number of participants, which is only 25 fishermen, the short duration of mentoring, and limited access to digital infrastructure so that the implementation of digital marketing is not yet evenly distributed. Contribution: This program contributes by providing a model for empowering fishermen based on branding strategies and digital technology that can be replicated in other coastal areas. Furthermore, the program enhances fishermen's capacity in business management, product diversification, and digital marketing skills, thereby increasing the competitiveness of local products. The program also supports post-disaster food security by strengthening community-based production chains and opening access to food certification to add value and expand markets.